Analisis Kesalahan Siswa Olimpiade MTsN 2 Kediri dalam Menyelesaikan Soal Cerita Ditinjau dari Tahapan Newman Tahun Ajaran 2018/2019 - Asyhar, Beni; Sholihah, Ummu; Munawaroh, Siti Lailiatul (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 3 No 1 (2019): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami), 2020)
The phenomenon of the many olympic students in Islamic Junior High School 2 in Kediri who made mistakes in solving story problems repeatedly and continuously. Whereas in solving students' word problems through stages that can be viewed from the Newman stage, which can be analyzed when students make mistakes in a stage. The Newman stage consists of reading, comprehension, transformation, skill process and encoding. In this case, there is a need for research that analyzes errors made by olympic students of the MTsN 2 Kediri academic year 2018/2019. The purpose of this study is to describe the mistakes of olympic students of the Islamic Junior High School 2 Kediri type of visual, auditory, and kinesthetic learning in solving word problems in terms of the stages of Newman. This research includes qualitative research, data collection is done by using questionnaires, tests, and interviews. The analysis technique used is data reduction, data presentation, and conclusion drawing. The population is olympic students of the Islamic Junior High School 2 Kediri, with questionnaires and test samples totalling 37 and interview samples of 6 students. The results of the study show, (1) Errors of olympic students of the MTsN 2 Kediri type of visual learning in solving word problems in terms of stages Newman makes different mistakes but occurs in all steps namely reading, comprehension, transformation, skills process, encoding. (2) Errors of olympic students of the MTsN 2 Kediri types of auditory learning in solving word problems in terms of stages Newman makes different mistakes but occurs in all steps, namely reading comprehension, transformation, skill process, encoding (3) errors of olympic students of the MTsN 2 Kediri types of kinesthetic learning in solving word problems in terms of the stages of Newman only make reading errors, transformation errors and skill process errors